Spirituality in Organizations? - Tecchio, Edivandro Luiz; Cunha, Cristiano José Castro de Almeida; Santos, Fabiana Besen (Organizações & Sociedade, 2016)
This article aims to describe how organizational spirituality has been dealt with in national and international research. Thus, a review of literature was carried out, based on a systematic search on literature on the Scopus and SciELO databases. The survey revealed 551 articles, but only 118 were available as full-documents. After reading the articles, 72 were selected for analysis. From the selected articles, seven major themes were identified and are covered in this article: factors that encourage spirituality to develop in organizations; the differences between spirituality and religion; the definition/concept of organizational spirituality; the benefits of spirituality for organizations; the dimensions of spirituality in organizations; the values of spirituality in organizations, and ways of identifying/ measuring spirituality in organizations. In general, it was found that the theme of organizational spirituality is gaining momentum among academics and managers and can no longer be ignored. Although research performed until now has provided encouraging results, more research is required, including empirical research, in order to elucidate and consolidate an understanding of the theme, as well as its importance for people and organizations.